PERAN ADVOKAT DALAM PENYELESAIAN SENGKETA DILUAR PENGADILAN MELALUI MEDIASI - Mantoma Tawanda Daeli; Martono Anggusti (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Dispute resolution through mediation is an alternative method outside of court proceedings that offers faster, more efficient, and amicable solutions between parties. Lawyers, as legal professionals, play a crucial role in assisting clients or acting as mediators in the mediation process. This study aims to analyze the strategic role of lawyers in mediation and the effectiveness of their involvement in peacefully resolving disputes outside the judiciary. The research uses a normative juridical method with a statutory and literature approach. The results indicate that lawyers are not only legal representatives but can also serve as neutral and professional mediators in accordance with Law Number 18 of 2003 on Advocates and relevant Supreme Court regulations. Their role in mediation contributes to more efficient dispute resolution, reduces the burden on courts, and supports the creation of restorative justice